Modern issues of oncofertility and oncoreproduction - I. A. Petrov; E. O. Churkin; Ya. I. Arkhipova; A. L. Chernyshova; A. A. Chernyakov; N. V. Sevostyanova (Опухоли женской репродуктивной системы)
The problem of the occurrence of malignant neoplasms in women of reproductive age has not only medical, but also extremely important social significance, as it affects the demographic potential of the country as a whole.The article presents an analysis of the current state of the problem of fertility and preservation of reproductive function in cancer patients. Currently, there are a sufficient number of methods of assisted reproductive technologies aimed at preserving fertility in women with cancer. Among them are the following: cryopreservation of embryos and oocytes, ovarian tissue, in vitro maturation of eggs, obtaining oocytes obtained by removing the ovaries with their subsequent maturation. In addition, auxiliary methods are also distinguished, the main purpose of which is ovarian protection: the use of gonadotropin-releasing hormone agonists, ovarian transposition, gonadal screening. Each method has its advantages and disadvantages. It should be noted that the very fact of the presence of oncological pathology makes its own adjustments to the use of each specific technique. It has been shown that in vitro maturation technology is the most optimal for the preservation and realization of reproductive function in cancer patients. One of its few disadvantages is the high cost and complexity of laboratory control and cultivation of oocytes, which undoubtedly requires highly qualified specialists and relevant experience.